Circulation Marine De La Baie De Dakhla (Sud Du Maroc) Par Modèle Hydrodynamique 2d - Karim, Hilmi; Abdellatif, Orbi; Ahmed, Makaoui; Hassan, Bouksim; Mohammed, Idrissi; Omar, Ettahiri; Benyounes, Abdellaoui; Mustapha, Ait Chattou (European Scientific Journal, ESJ, 2017)
The marine circulation of Dakhla bay (South of Morocco 23°30’N- 16°W) have been studied from January to February 2010 by 2D hydrodynamic model. This study aims to understand the marine circulation of this bay and its hydrodynamic functioning. Mainly governed by M2 tide and during spring tides, tidal currents are very strong in intensity near the inlet of the bay and its surrounding (between 1 and 2 m.s-1). In its central part and the nothern part of the bay, their intensity are very less (< 1 m.s-1). During neap tides, tidal currents are less in intensity (< 0.6 m.s-1) in all the areas of the bay.